The global burden of cardiovascular diseases attributable to high body mass index, 1990–2023 - Sun, Manqi; Shi, Yue; Li, Na; Zhou, Ziyang; Luo, Jiahong; Chen, Zaozao; Lin, Duo; Tan, Rubin (Frontiers in Cardiovascular Medicine, 2026)
ImportanceObese patients are mostly accompanied by various cardiovascular diseases (CVDs), which is a major global health challenge and has important clinical significance. The global burden of CVDs caused by high body mass index (BMI) is still not well known.ObjectiveTo determine the global burden of high BMI-related CVDs from 1990 to 2023.MethodsFollowing the methodological framework and analytical strategy used in the 2023 global burden of disease study (GBD 2023), we examined the death and disability-adjusted life years (DALYs) of CVDs associated with high BMI in the global population considering year, gender, age, socio-demographic index (SDI), income, and geographic location. We also calculated the annual percentage change (APC) to quantify the trends over time.ResultsFrom 1990 to 2023, high BMI significantly contributed to over a 2-fold increase in global deaths and DALYs due to CVDs, particularly affecting ischemic heart disease (IHD), hypertensive heart disease (HHD), ischemic stroke (IS), and intracranial hemorrhage. IHD saw a doubling of deaths and DALYs, with males being more affected, and the age group with the highest deaths in over 70 years old, while DALYs peaked in the 50–69 age group. The deaths of IHD moved from high SDI to upper-middle SDI countries. Deaths and DALYs for HHD, IS, and intracranial hemorrhage also doubled, with females being slightly more affected. These conditions maintained their highest death in those over 70, but DALYs were highest in the 50–69 age group. The fastest-growing APC of deaths and DALYs were observed in low SDI countries and regions, as well as lower-middle income countries and regions, indicating a significant shift in the geographic distribution of CVD death.ConclusionHigh BMI is a major contributor to CVDs globally, leading to significant increases in deaths and DALYs over the past three decades. The impact varies by age, gender, income level, and geographic region, with the APC growing most rapidly in lower-middle income populations. IHD is particularly concerning, with notable gender and age-specific trends. Addressing high BMI and its associated cardiovascular risks, especially in vulnerable populations, is crucial to mitigating the growing impact of obesity-related CVDs.